The distribution of Hypocretin/Orexin receptor mRNA in the mouse and human brain - Sanjida Mir; Ryan J. Keenan; Romke Bron; Cameron J. Nowell; Catriona McLean; Leah C. Beauchamp; Laura J. Vella; Brian Dean; Daniel Hoyer; Laura H. Jacobson (Elsevier, 2024)
Hypocretin (Hcrtr, HCRTR) / orexin (OX) receptors modulate a range of neurobiological functions and are drug targets for several disorders. Mapping the distribution of receptors in the brain can inform their function and guide targeting of specific disorders. Although studied in rodents, orexin receptor distribution has remained relatively unexplored in humans, and thus there is also a paucity of comparative anatomy. The aim of this study was therefore to map the distribution of hypocretin/orexin receptor mRNA in selected regions of the mouse and human brain by non-radioactive in situ hybridization (ISH) using digoxigenin (DIG)-labelled cRNA anti-sense probes. Data revealed both distinct and overlapping patterns of distributions of Hcrtr1/HCRTR1 and Hcrtr2/HCRTR2 mRNA suggesting that the functions of the orexin system are mediated differently by each receptor. In the mouse brain, the highest expression of Hcrtr1 mRNA was in the locus coeruleus (LC) whereas Hcrtr2 mRNA was most abundant in the lateral hypothalamus (LH). The human caudate nuclei showed significant expression of both HCRTR1 and HCRTR2 mRNA, whereas the mouse predominantly expressed Hcrtr2 mRNA. The noradrenergic neurons of the human LC showed high signals for both HCRTR1 (71.7%) and HCRTR2 (81.5%) mRNA. Expression of HCRTR2 mRNA in non-noradrenergic human LC cells was also notable. The distribution pattern in mouse and human brains is consistent with the involvement of the orexin system in arousal and the sleep/wake cycle in both species, however, variations in receptor subtype expression profiles suggests that species differences in responses to orexin receptor ligands may be expected.